DESCRIPTION OF SPERM DNA FRAGMENT WITH EMBRYO IN IVF PATIENTS - Selvia Selvia; Harini Nurcahya Mariandayani; Rina Puspita; Sari Artauli Lumban Toruan (NHM PRESS, 2023)
Infertility is a condition in couples married husband and wife have had sexual intercourse regularly and adequately for more than one year without using contraception but have not had a pregnancy or offspring. Factors that cause infertility can be caused by male factors, female factors and even both. Male contributors are 40% -50%. Analysis of DNA fragmentation of sperm with embryo development aims to determine the description of DNA fragmentation of sperm with embryo development in patients with IVF programs. This study used 30 samples of married men carrying out a pregnancy program (IVF) who met the inclusion criteria.